Marrow adipose tissue is increased in overweight and obese women with PCOS independently of hyperandrogenism related obesity and metabolic disorders - Xu, Li; Min, Min; Li, Xintong; Blake, Glen M.; Zhao, Kaiping; Ruan, Xiangyan; Cheng, Xiaoguang (Frontiers in Endocrinology, 2023)
Purpose: This study aimed to investigate the increase in bone marrow adipose tissue (BMAT) in overweight and obese women with polycystic ovary syndrome (PCOS) and its relationship with hyperandrogenism, obesity, and metabolic disorders. Methods: The study included 87 overweight or obese women with PCOS (mean age 29 ± 4 years), as well as 87 age-matched controls recruited from a separate population study. All PCOS patients were measured for anthropometric features, abdominal adipose tissue areas, BMAT, biochemistry, and sex hormones. BMAT was compared between the PCOS patients and controls. In PCOS patients, subgroup comparisons of BMAT and its associations with body adiposity indices, biochemistry, and sex hormones were analyzed. The odds ratios (ORs) of elevated BMAT (defined as BMAT ≥ 38%) were calculated. Results: On average BMAT was increased by 5.6% (±11.3%) in PCOS patients compared to controls. BMAT were significantly higher in the upper tertiles of total cholesterol (TC) and low density lipoprotein-cholesterol (LDL-C). BMAT was not correlated with abdominal adiposity indices or biochemistry except for LDL-C (r = 0.253—0.263, p = 0.014—0.018). LDL-C was not significantly different between the normal and abnormal androgen PCOS subgroups (p = 0.10-0.887). LDL-C, follicle stimulating hormone (FSH), and total testosterone (TT) were risk factors for elevated BMAT, with ORs of 1.899 (p = 0.038-0.040), 1.369 (p = 0.030-0.042), and 1.002 (p = 0.040-0.044) for each unit increase, respectively. Conclusion: BMAT was increased in overweight and obese PCOS patients, but the increase in BMAT was not associated with the hyperandrogenism related obesity or metabolic disorders.